Vitamin D Uptake in Patients Treated with a High-Dosed Purified Omega-3 Compound in a Randomized Clinical Trial Following an Acute Myocardial Infarction - Naesgaard, Patrycja A.; Grundt, Heidi; Nordøy, Arne F.; Staines, Harry; Nilsen, Dennis W. T. (Frontiers in Cardiovascular Medicine, 2017)
Background: Fish is the natural dietary source of vitamin D. Reports on the influence of purified omega-3 fatty acids on its uptake are scarce. Objectives: We investigated the impact of a purified high-dosed omega-3 compound compared to omega-6 on 25-hydroxyvitamin D [25(OH)D] levels following an acute myocardial infarction. Methods: 228 patients were randomized 1:1 to receive a daily dose of either 4 g omega-3 (OMACOR®) or an equal dose of omega-6 (corn oil), administered double-blindly for 12 months. Total omega-3 and omega-6 measurements were available in 40 randomly picked patients. Results: There was no significant intergroup difference in 25(OH)D changes during follow-up (p = 0.12), but there was a minor statistical significant intragroup increase of 25(OH)D in both intervention arms (p < 0.001 for n-3 PUFAs and p = 0.013 for corn oil, respectively). A positive correlation was noted between 25(OH)D and omega-3 prior to inclusion; r = 0.418, p = 0.007, attenuated at 12 months by purified omega-3 intervention; r = 0.021, p = 0.93. No positive correlation was observed between omega-6 and 25(OH)D. Conclusion: Long-term treatment with a high dose of purified omega-3 as compared to corn oil did not improve serum concentrations of vitamin D.